Immunoparesis in multiple myeloma: a current overview - Wang, Hongfeng; Chen, Jianbin (Frontiers in Oncology, 2025)
Multiple myeloma (MM) is a common hematologic malignancy characterized by clonal plasma cell proliferation. Despite significant therapeutic advancements with proteasome inhibitors, immunomodulatory drugs, and anti-B-cell maturation antigen (BCMA) therapies, the disease remains largely incurable. Immunoparesis, a severe state of immune dysfunction, exhibits high prevalence in MM patients and profoundly impacts prognosis. This review summarizes the pathogenic mechanisms and clinical characteristics of immunoparalysis, with a focus on its impact on prognosis and early-onset infections, the effects of contemporary drug therapies on immunoparalysis, and immune reconstitution.